2011
DOI: 10.5415/apallergy.2011.1.2.80
|View full text |Cite
|
Sign up to set email alerts
|

Clinical features of the extrinsic and intrinsic types of adult-onset atopic dermatitis

Abstract: BackgroundMost study concerning the prevalence and dermatological manifestations of the extrinsic and the intrinsic form of atopic dermatitis (AD) were performed in children and adult AD related to the early-onset AD extending to adult life. Adult-onset AD is a subgroup of AD. Apart from the typical eczematous flexural distribution pattern of AD, this group may also have nontypical morphology and localization.ObjectiveThe purpose of this study was to compare the clinical and diagnostic features of Thai patient… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

3
51
2
4

Year Published

2013
2013
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 51 publications
(60 citation statements)
references
References 19 publications
3
51
2
4
Order By: Relevance
“…Although the intrinsic form has been considered by some as a step toward the development of extrinsic form, it is becoming increasingly clear that it may actually represent a different subtype [5]. No difference in severity of disease is typically observed between the two subsets of patients although different frequency in distribution of lesions has been described [7]. The intrinsic form tends to develop in older patients and filaggrin mutations are not a characteristic of this form [8].…”
Section: Atopic Dermatitis: Comparative Observationsmentioning
confidence: 99%
“…Although the intrinsic form has been considered by some as a step toward the development of extrinsic form, it is becoming increasingly clear that it may actually represent a different subtype [5]. No difference in severity of disease is typically observed between the two subsets of patients although different frequency in distribution of lesions has been described [7]. The intrinsic form tends to develop in older patients and filaggrin mutations are not a characteristic of this form [8].…”
Section: Atopic Dermatitis: Comparative Observationsmentioning
confidence: 99%
“…Fölster-Holst et al [13] and Brenninkmeijer et al [14] observed intrinsic AD to have a later age at onset and milder disease severity when compared to extrinsic AD. However, Kulthanan et al [12] found no difference in the disease severity between the two groups and both extrinsic and intrinsic AD had an early age at onset in their study. Thus intrinsic AD is uncommon in adults unlike in children.…”
mentioning
confidence: 94%
“…[11] Extrinsic AD is more common in adult onset AD (87.5-93.05%) and the prevalence of intrinsic AD tends to be higher in younger individuals (15-45%) when compared to adults (5.4-12.5%). [12,13] This could probably be due to the delayed appearance of respiratory allergies signifying the atopic march in children, or it could be that some forms of intrinsic AD are triggered by sensitization to completely different antigens or it could be that very young children have a transient form of spontaneously resolving eczema that is not a typical AD.…”
mentioning
confidence: 96%
See 2 more Smart Citations